Brief on the Planned United Fiber System (UFS) pulp mill project for South Kalimantan, Indonesia - Jurgens, E.; Barr, C.; Cossalter, C. (Center for International Forestry Research, 2005)
United Fiber System, Ltd (UFS) seeks to secure financing for a 600,000 tonnes greenfield pulp mill project in South Kalimantan, Indonesia. It will be somewhat unique in Indonesia in that it will source its fiber entirely from sustainably managed plantations and will generate minimal negative impacts on natural forests and local communities. This brief has been prepared to promote a more informed and transparent dialogue on the proposed project among financial decision makers, policy makers, and other stakeholders. Based on a review of available documents and analyses, CIFOR has major questions regarding the social and environmental sustainability of the planned pulp mill and associated plantations. The issues are first limited information on the plantation development program provided by UFS. Secondly, the proposed project is likely to place direct pressures on the 77,000 ha of natural forest that reportedly remains at the PT Hutan Rindang Banua (PT HRB) plantation concession, and particularly on the 44,000 ha of areas covered by ‘mixed tropical hardwood’ (MTH) that were designated by Jaakko Poyry to be appropriate for plantation development. Thirdly, the development of a new 600,000 tonne pulp mill in South Kalimantan would compound the very significant problem of industrial over capacity that currently exists in Indonesia’s forestry sector. Fourth, while the proposed pulp mill and associated plantations could generate significant employment and associated benefits, there is a risk of serious negative impacts on surrounding communities, which have a population of over 60,000 people. Finally, the project’s current ownership structure lacks transparency, and this could lead to a lack of accountability if UFS or its affiliates fail to meet the commitments it is now making. As such, it is essential that financial decision makers, policy makers, and other interested parties design structures for ensuring accountability and transparency on the part of project principals.